Impaired and restored CD8+ T cell responses to a sequentially mutated spike epitope in Omicron variants - Chung, Eun Joo; Park, Soyoung; Kim, Su-Hwan; Choi, Ju-yeon; Jeong, Hye-Sook; Ko, Jae-Hoon; Song, Joon Young; Lee, Young Jae (Frontiers in Immunology, 2025)
In the post-pandemic era, SARS-CoV-2 variants continue to circulate and evolve. T cell-mediated immunity is essential for antiviral defense, but its evasion by emerging variants remains poorly defined. In this study, we screened spike-derived CD8+ T cell epitopes using bioinformatic algorithms and validated them experimentally in COVID-19 vaccine recipients. LYNSASFSTF (LYN), located in the receptor-binding domain (S368–377), was identified as an HLA-A*24:02-restricted epitope harboring mutations observed in Omicron BA.1 (S371L, S373P, and S375F) and BA.2 (S371F, S373P, S375F, and T376A). BA.2 mutations more profoundly attenuated LYN-specific cellular immunity than those from BA.1 with T376A as a major contributor to immune evasion, as supported by structural analysis of altered peptide–HLA interactions. This effect was mitigated by BA.1/BA.2 breakthrough infection and appears unlikely to persist in the currently dominant NB.1.8.1 lineage, where the LYN sequence remains conserved. Our findings suggest that LYN may function both as an immune-evasive hotspot and as a cross-reactive epitope, underscoring the importance of continued epitope-level surveillance as future variants emerge.